PENGGUNAAN APLIKASI QUIZIZZ PADA MATA PELAJARAN AL-QUR’AN HADITS UNTUK MENINGKAKAN MINAT BELAJAR SISWA MADRASAH ALIYAH NEGERI SIDOARJO - Mufaizah; M Nur Wahid; Zidni Akholik Almaghfiroh; Wanda Citra Dewi; Irfan Nofa Sagita; Laela Nur Afifah; Moh. Ainun Najib (Global Action and Education for Society, 2026)
This study aims to describe the use of the Quizizz application in increasing student learning interest in the Al-Qur'an Hadith subject at MAN Sidoarjo. This study uses a qualitative method with a literature study approach through a review of various journals, scientific articles, and research results relevant to gamification-based learning technology. The focus of the study includes the use of the Quizizz application as an interactive learning medium and its influence on indicators of student learning interest. The results of the study indicate that Quizizz is able to create a more interesting learning atmosphere through interactive quiz features, varied visual displays, and fun evaluation mechanisms. Through elements of competition and direct feedback, Quizizz has been proven to increase student enthusiasm, attention, and involvement in the Al-Qur'an Hadith learning process. Based on these findings, Quizizz is considered to have the potential to be an effective and relevant learning medium in supporting the learning process in madrasas, especially in efforts to increase student learning interest.